Smart Pickering Emulsions Co-Stabilized by Chalcogenoviologen Surfactants and Single-Atom Pt-Decorated g-C3N4 for Switchable Biphasic Photocatalysis - Zhaohui Cui; Siyu Sun; Tianyue Yuan; Lijie Ding; Xiang Han; Qi Sun; Zhaoguang Zhang; Hanchang Lu; Houbing Zou; Yawen Li; Ruyi Zheng; Gang He (Journal of the American Chemical Society, 2026)
Abstract Interfacial reaction microenvironments play a critical role in determining photocatalytic performance beyond the intrinsic properties of photocatalysts. However, emulsion-based photocatalytic platforms that simultaneously offer structural robustness, switchable operation, and efficient interfacial charge-transfer regulation remain rare. Herein, smart-responsive Pickering emulsions are developed by costabilization of chalcogenoviologen surfactants (SV2+-UDA/SeV2+-UDA/TeV2+-UDA) and single-atom platinum-decorated graphitic carbon nitride (Pt SAs@g-C3N4) for biphasic photocatalysis. The resulting emulsions exhibit outstanding stability in strong acidic and alkaline media as well as in saturated brine while allowing reversible demulsification and re-emulsification under an external electric field, thereby enabling switchable catalysis and catalyst recovery. The optimized emulsion achieves a hydrogen evolution rate of up to 7824 μmol·h–1·g–1 under visible-light irradiation, corresponding to a 3.0-fold enhancement over the bulk aqueous, viologen-free system, while retaining over 90% of its activity across a wide pH range and under seawater salinity. More importantly, the emulsion functions as a bidirectional microreactor, coupling aqueous hydrogen evolution with oil-phase oxidative coupling of benzylamine without sacrificial reagents, and delivers imine yields above 85% together with a hydrogen evolution rate of 3892 μmol·h–1·g–1. The enhanced performance highlights the critical role of interfacial synergy. The surfactant/photocatalyst costabilization strategy provides a versatile platform for robust, switchable, and synergistic biphasic photocatalysis.